Clinical and serological features of patients with dermatomyositis complicated by spontaneous pneumomediastinum. Issue 2 (February 2016) - Ma, Xiaolei; Chen, Zhiyong; Hu, Wei; Guo, Ziwei; Wang, Yan; Kuwana, Masataka; Sun, Lingyun
Abstract The purpose of this study was to explore the clinical and serological features of patients with pneumomediastinum (PNM) and dermatomyositis-associated interstitial lung disease (DM-ILD). A total of 93 patients (68 with classic DM and 25 with clinically amyopathic DM [CADM]) were recruited. Clinical and laboratory data were collected retrospectively. Anti-melanoma differentiation-associated gene 5 (MDA5) antibodies were detected using enzyme-linked immunosorbent assay (ELISA). Variables were compared between patients with and those without PNM. Multivariate analysis was performed using a multivariate logistic regression model. A total of 11 patients developed spontaneous PNM. During the follow-up period, 6 patients died of respiratory failure. No differences in sex, age at the onset of DM, serum ferritin levels, and C-reactive protein (CRP) levels were observed between DM patients with and without PNM. Compared with DM patients without PNM, those with PNM had significantly higher frequencies of rapidly progressive ILD (RP-ILD) (63.6 vs 24.4 %, P  = 0.01), anti-MDA5 antibodies (90.9 vs 52.4 %, P  = 0.02), CADM diagnoses (63.6 vs 22.0 %, P  = 0.007) and cutaneous ulcers (36.4 vs 11 %, P  = 0.04), but significantly lower creatine kinase (CK) levels (58.5 vs 284 U/l, P  = 0.04). The multivariate analysis indicated that cutaneous ulcer was the only independent risk factor for the occurrence of PNM in DM (OR = 5.98, 95 % confidence interval [CI] 1.12–31.98, P  = 0.037). PNM is a refractory complication and tends to occur in DM patients with RP-ILD, anti-MDA5 antibody, CADM diagnosis, and low CK level, and especially in patients with cutaneous ulcers.